Hypersensitive antibiotic susceptibility test based on a beta-lactamase assay with a parylene-matrix chip - Park, Jong-Min; Kim, Jo-Il; Noh, Joo-Yoon; Kim, Mira; Kang, Min-Jung; Pyun, Jae-Chul (ELSEVIER SCIENCE INC, 2017)
Many kinds of susceptibility test for P-lactam antibiotics have been used to determine the antibiotic resistance of bacterial strains. Here, a sensitive antibiotic susceptibility test was presented by using a specialized reaction tool for laser desorption/ionization time-of-flight mass spectrometry (LDI-TOF MS) based on parylene-matrix chip. The p-lactamase assay was carried out in a specialized reaction tool by (1) concentrating the bacterial strain and (2) incubating the bacteria with penicillin-G. The parylene-matrix chip was produced by deposition of a partially porous parylene-N thin film on a dried organic matrix array, and the products of p-lactamase reaction in the low range of mass-to-charge ratio (m/z< 500) could be effectively analyzed by using a parylene-matrix chip. The sensing parameters were compared with conventional chromogenic antibiotic susceptibility test for beta-lactam antibiotics. Finally, LDI-TOF MS with a specialized reaction tool and parylene-matrix chip could achieve a limit of detection as low as 600 cells/spot for penicillin-G. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: FLIGHT MASS-SPECTROMETRY; AUTODISPLAYED Z-DOMAINS; COLI OUTER-MEMBRANE; BACTERIAL SUSCEPTIBILITY; SPR BIOSENSOR; E. COLI; IMMOBILIZATION; IMMUNOASSAY; LAYER; FILM